APLIKASI INVENTORI BARANG DENGAN METODE AVERAGE - irawan, indra (CV. Hawari, 2021)
With the rapid use of computer technology in business transactions, the author is interested in conducting a study that discusses the inventory system of building materials using the average method. With the use of this method in the process of calculating stock of goods, it is expected to be able to help business people in sustaining and developing the business they pioneered, so that they can compete with other similar business actors. This is illustrated from the transfer of the manual calculation process into the automation process resulting from the system built, the process of retrieving information that is fast, precise and accurate will be very helpful in terms of decision making, so that the targets to be achieved can be more easily and quickly implemented. In the future, this inventory information system can be developed again with a wider scope with a larger organizational scope.